The South Kalimantan Provincial Election Commission's Strategy to Increase First-Time Voters in the 2024 South Kalimantan Gubernatorial Election - Ramadani, Mustafa (Westscience Press, 2025)
This study examines the strategy of the General Elections Commission (KPU) of South Kalimantan Province in increasing the participation of first-time voters in the 2024 South Kalimantan Gubernatorial Election (Pilgub). The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with KPU South Kalimantan commissioners and data obtained from official KPU South Kalimantan reports. The results show that the KPU South Kalimantan implemented a multidimensional political communication strategy through educational, participatory, and digital approaches. Several main programs carried out included the Election Procession activities, the launch of the